Efeito antitumoral e toxicidade de um novo derivado acridínico (AMTAC-17) em modelos in vitro e in vivo - Silva, Daiana Karla Frade (2020)
Cancer is a term that refers to a set of diseases characterized by the uncontrolled proliferation of cells, capable of invasion and metastasis. Despite the progress in oncology’s researches, there are still many issues in the therapies employed, such as high toxicity and the development of resistance to current treatments. Considering the reports in the literature of antitumor activity of acridine derivatives, the present work aimed to investigate the toxicity and antitumor activity in vitro and in vivo of a new spiroacridine compound, the (E)-5'-oxo-1'-((3,4,5-trimethoxy-benzylidene)amino)-1',5'- dihydro-10H-spiro[acridine-9,2'-pyrrole]-4'-carbonitrile (AMTAC-17), selected after pharmacological screening. The in vitro antitumor activity was evaluated by the MTT reduction test (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide), obtaining a 50% inhibitory concentration value (IC50) of 27.19 µM against the colon cancer strain HCT-116. In vitro toxicity was assessed in HaCaT, L929 cells and Peripheral Blood Mononuclear Cells (PBMC) (IC50: 31.40 µM, 103.50 µM, and 18.62 µM, respectively). At concentrations of 30 and 60 µM in HCT-116 cells, AMTAC-17 altered the progression of the cell cycle, inducing an increase in the sub-G1 peak, indicative of cell death due to apoptosis, confirmed by the externalization of phosphatidylserine and morphological changes such as the formation of prolongations in the cell membrane, chromatin condensation, and nuclear fragmentation, as also by inducing a reduction in the level of reactive oxygen species (ROS). In the fish embryo toxicity test (FET test), the average lethal concentration (LC50) of AMTAC-17 was greater than 300 µM. In the acute non-clinical toxicity test in mice, AMTAC-17 (2000 mg/kg; intraperitoneal route, i.p.) did not induce death of the experimental animals, with 50% lethal dose (LD50) being estimated as greater than 5000 mg/kg. The micronucleus test was performed in mouse peripheral blood, and it was observed that AMTAC-17 (2000 mg/kg, i.p.) did not cause an increase in the number of micronucleated erythrocytes, indicating low genotoxicity. In the antitumor activity in vivo, in a model of Ehrlich's Ascitic Carcinoma (CAE), it was observed that AMTAC-17 (12.5; 25 or 50 mg/kg, i.p., seven days of treatment) reduced the viability and the total peritoneal tumor cells. AMTAC-17 (12.5 mg/kg) induced an increase in the sub-G1 peak, related to apoptosis, reduced peritumoral vascular microdensity, indicating antiangiogenic action, as well as increased levels of IL-1β, TNF-α, and IL-12 cytokines, which is associated with immunomodulatory capacity. In vivo, AMTAC-17 did not change ROS levels. Regarding toxicity after antitumor treatment, among all the parameters evaluated (metabolic, biochemical, hematological and histological parameters), it was observed that AMTAC-17 (12.5 mg/kg) did not induce significant changes. The data presented indicate that AMTAC-17 has antitumor activity in HCT-116 cells, by inducing apoptosis and promoting antioxidant effect, and promoting antiangiogenic and immunomodulatory action in vivo, associated with low non-clinical toxicity.